Delivering WASH education at scale: evidence from a global MOOC series. (April 2021) - Suter, Fabian; Lüthi, Christoph
The water, sanitation and hygiene (WASH) sector is facing a shortfall of several million appropriately skilled professionals. Massive open online courses (MOOCs) can play a crucial role in addressing this. This paper presents the case study of the MOOC series "Sanitation, Water and Solid Waste for Development", which has reached over 120, 000 learners within six years. It has attracted mainly well-educated, employed learners, under 34 years old, from Asia, Latin America and Africa. Underrepresentation of female learners remains a challenge. While MOOCs have proven excellent for delivering WASH education at scale, some alternative formats (e.g. blended learning, small private online courses) allow more collaborative, interactive learning environments. Three practical examples from Nigeria, Indonesia and Mozambique indicate the potential for synergies among MOOCs and further learning formats. With the global shift towards digital learning due to the COVID-19 pandemic, MOOCs have gained further traction.